2022
DOI: 10.3390/ph15121554
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Some Nutraceuticals against Manganese-Induced Parkinson’s Disease in Rats: Possible Modulatory Effects on TLR4/NLRP3/NF-κB, GSK-3β, Nrf2/HO-1, and Apoptotic Pathways

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder affecting the substantia nigra where functions controlling body movement take place. Manganese (Mn) overexposure is linked to a neurologic syndrome resembling PD. Sesamol, thymol, wheat grass (WG), and coenzyme Q10 (CoQ10) are potent antioxidants, anti-inflammatory, and anti-apoptotic nutraceuticals. We investigated the potential protective effects of these nutraceuticals alone or in combinations against MnCl2-induced PD in rats. Seven groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…Furthermore, besides TLR4‐dependent processes, we did not explore other potential mechanisms in this study. For instance, the nuclear factor‐erythroid 2‐related factor 2 (Nrf2) pathway reduces OS by manipulating antioxidant proteins such as heme oxygenase‐1, mitigating inflammation, and inhibiting Aβ and tau phosphorylation, which enhances memory, learning, and cognitive abilities 34,35 . Research has also reported that miR‐146a induces OS through the MAPK signaling pathway, exacerbating cognitive impairment and AD pathology 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, besides TLR4‐dependent processes, we did not explore other potential mechanisms in this study. For instance, the nuclear factor‐erythroid 2‐related factor 2 (Nrf2) pathway reduces OS by manipulating antioxidant proteins such as heme oxygenase‐1, mitigating inflammation, and inhibiting Aβ and tau phosphorylation, which enhances memory, learning, and cognitive abilities 34,35 . Research has also reported that miR‐146a induces OS through the MAPK signaling pathway, exacerbating cognitive impairment and AD pathology 36 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Similarly, Abu-Elfotuh et al found that oral thymol administration at the final dose of 15 mg/kg/day for 5 weeks (i.e., 35 days) could effectively improve neuronal degeneration and behavioral impairments in rats via the inhibition of oxidative stress, apoptotic cell death, and neuroinflammatory response in the brain tissues of rats with Parkinson's Disease. 28 Thymol has also shown promise in mitigating cognitive deficits and brain damage induced by heavy metals or high-fat diets. 28−31 Furthermore, studies also showed that a thymol diet of up to 500 mg/kg in rats exhibited no toxicity, indicating higher safety.…”
Section: Introductionmentioning
confidence: 99%
“…4 Progressive loss of dopaminergic neurons in the midbrain, a main cause of PD, may result in concomitant dopamine depletion and α-synuclein accumulation. 5 Besides, it is believed that neuroinflammation and oxidative stress also act key roles in PD pathogenesis, 6 suggesting anti-oxidative and anti-inflammatory agents might offer a promising therapeutic potential for PD. Since current drugs for PD treatment mainly target PD symptoms and cannot prevent the loss of dopaminergic neurons, 7 the discovery and development of novel neuroprotective and disease-modifying agents for PD are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, major PD symptoms include motor dysfunctions (e.g., bradykinesia, rest tremor, and muscular rigidity) 4 . Progressive loss of dopaminergic neurons in the midbrain, a main cause of PD, may result in concomitant dopamine depletion and α‐synuclein accumulation 5 . Besides, it is believed that neuroinflammation and oxidative stress also act key roles in PD pathogenesis, 6 suggesting anti‐oxidative and anti‐inflammatory agents might offer a promising therapeutic potential for PD.…”
Section: Introductionmentioning
confidence: 99%